Impact of indium ions on some properties of TiO2 thin films for sensor applications. (2022) - Doubi, Youssef; Hartiti, Bouchaib; Siadat, Maryam; Arba, Youssef; Stitou, Mohamed; Labrim, Hicham; Nkuissi, Hervé Joël Tchognia; Fadili, Salah; Tahri, Mounia; Thevenin, Philippe; Losson, Etienne
Abstract: Indium doped Titanium dioxide (TiO2 : In) thin layers were deposited on glass substrates by the spray pyrolysis deposition with the substrate temperature 450 °C. The structural and the optical properties studies were investigated for the films deposited with various atomic doping indium percentage (0, 1, 3, 5 and 7 at.%). The results of X-ray diffraction (XRD) was shown the presence of anatase peak with a strong orientation along (1 0 1) plane. The crystallite size was found to be between 7.09 and 14.43 nm. Raman spectroscopy of undoped and doped TiO2 thin films were confirmed the presence of single phase of anatase TiO2 . The optical properties were determined using absorbance and transmittance results in the range of wavelength between 300 and 800 nm. The calculated optical band gap varied between 3.08 and 3.25 eV. The Hall measurement displayed an increase of conductivity 1.04 to 5.03 Ω −1 .cm −1 and the electron mobility from 11.33 to 35.70 cm 2 /V.s in front of the decrease of the resistivity from 9.56 × 10 −1 to 1.98 × 10 −1 Ω.cm for the variation of atomic doping from 0% to 7%. The best obtained properties of undoped and doped TiO2 make our sprayed thin films suitable to be as sensitive layer for optoelectronic applications among these, a gas sensor application.